27-y:25 points
Step-by-step explanation
Step 1
Let y represents the points she scored in the second half
total = 27 points
we also know that
total poitns= points first half+points sencond half
replace
![\begin{gathered} 27=\text{ points first half+y} \\ \text{now, subtrac y in both sides} \\ 27-y=\text{ Point first half} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/twhbqhcrc4cf41ndnkurzzlbdokwsqjdc5.png)
therefore, the expression is
![27-y](https://img.qammunity.org/2023/formulas/mathematics/high-school/7kjlb72td9vs8n6ldm48vbs5tjid2vnquf.png)
Step 2
now, if she scored 2 poitns in the second half
let
y=2
now, replace
![\begin{gathered} \text{ Points first half= 27-y=27-2=25} \\ so \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/b91oqmcfjdx9ejyzfwz1fbt18td5rk9qxx.png)
she scored 25 points in the first half
therefore, the answer is
27-y:25 points
I hope this helps you